Profil Higher Order Thinking Skills Mahasiswa dalam Memecahkan Masalah Geometri - Yunis Sulistyorini; Siti Napfiah; Nok Izatul Yazidah; Dian Fitri Argarini; Welas Listiani (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
HOTS is the ability to combine and develop newly acquired information and prior knowledge to solve non-routine problems. HOTS refers to the revised Bloom's Taxonomy which consists of analyzing, evaluating, and creating. However, this study was only analyzing (C4) and evaluating (C5). This study aimed to describe the HOTS profile of students in solving geometry problems. This type of research was descriptive qualitative research with the subject consisting of two students with high learning ability, each of whom was selected to represent two different Euclid Geometry classes. Data collection consisted of solving HOTS problems and unstructured interviews. The results showed that the two subjects had not been able to achieve high order thinking ability indicators. Students' higher-order thinking skills still need to be improved. Mathematics learning should designing considering the critical and creative thinking aspects to develop students' HOTS learning should be designed by considering critical and creative thinking aspects to develop students' HOTS.